2005
DOI: 10.1007/s00268-005-7859-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Nodules and Carcinomas in Patients Operated on for Renal Hyperparathyroidism: Experience with 339 Consecutive Patients and Review of the Literature

Abstract: The association between renal hyperparathyroidism (HPT) and differentiated thyroid carcinoma is discussed. To determine the prevalence and potential risk factors, we performed a retrospective analysis of our patients (1998-2004) and compared the data with the data from other surgical and autopsy studies. At our hospital, a total of 347 parathyroidectomies in 339 patients with renal HPT were performed. Most patients underwent preoperative ultrasound investigation of the thyroid gland and, if indicate, thyroid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
2
12
1
Order By: Relevance
“…Some authors have suggested that there is an association between secondary HPT and PTC (8,23). But in a large cohort study of 339 operated renal HPT cases from Germany, the prevalence of PTC (2.4%) has made an etiologic association between renal HPT and PTC unlikely (13). In our study, there was also no association between biochemically and=or histopathologically proven renal HPT and PTC.…”
contrasting
confidence: 72%
See 1 more Smart Citation
“…Some authors have suggested that there is an association between secondary HPT and PTC (8,23). But in a large cohort study of 339 operated renal HPT cases from Germany, the prevalence of PTC (2.4%) has made an etiologic association between renal HPT and PTC unlikely (13). In our study, there was also no association between biochemically and=or histopathologically proven renal HPT and PTC.…”
contrasting
confidence: 72%
“…In the same study, the frequency of thyroid tumors rose with the duration of dialysis. In another study, age and duration of dialysis were not found to be correlated with thyroid cancer development (13). In most autopsy studies in a normal population, a correlation with increasing age was found (14)(15)(16).…”
mentioning
confidence: 93%
“…In our study, favourable results on these parameters were observed. Most of the coincidental thyroid cancers were reported as PTC and in small size, particularly micro-papillary carcinoma [5,12,16,17]. Likewise, in our series, no need for further intervention was required due to majority of papillary microcarcinoma and small sized PTC without capsular infiltration.…”
Section: Discussionsupporting
confidence: 54%
“…However, an increased risk of non-parathyroid cancers in patients with pHPT has been reported in several studies [18]. Miccoli et al [13] reported thyroid malignancy as the most prevalent cancer among those patients in whom pHPT was [4,5,17,[19][20][21], others investigated several predisposing factors such as exposure to neck radiation, goitregenic effect and increased mitotic activity induced by hypercalcemia [22,23]. In addition, tumour-promoting effect of parathyroid hormone and subsequent genetic predisposition to new malignancies were also noted [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that the frequency of concomitant thyroid malignancy is lower than that in other studies. This could be explained partly by the fact that the relatively rarer use of neck irradiation therapy in China than in western country (Seehofer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%